Physician-reported Clinical Unmet Needs, Burden and Treatment Patterns of Paediatric Psoriasis Patients: A US and EU Real-world Evidence Study - Seyger, Marieke M.B.; Augustin, Matthias; Sticherling, Michael; Bachhuber, Teresa; Fang, Juanzhi; Hetherington, James; Lucas, James; Meakin, Sophie; Richardson, Craig; Paller, Amy S. (Acta Dermato-Venereologica, 2022)
This study is a retrospective analysis using data col-lected from the Adelphi Paediatric Psoriasis Disease-Specific Programme cross-sectional survey. Despite being treated for their psoriasis, a substantial proportion of paediatric patients presented with moderate (18.3%) or severe (1.3%) disease at sampling; 42.9% and 92.0% had a body surface area (BSA) of >10%, and 38.8% and 100.0% had a Psoriasis Area Severity Index (PASI) score >10, respectively. Overall, 69.9% of patients had only ever been treated with a topical therapy for their psoriasis. For patients with moderate or severe disease at sampling, 16.3% and 14.4% were currently receiving conventional systemics or biologic therapy, respectively. There is a clinical unmet need in this paediatric population; a considerable percen-tage of patients still experienced moderate or severe disease and persistent psoriasis symptoms, with nu-merous body areas affected. A significant proportion of patients were undertreated, which may explain the high burden of disease observed.
CRIS-Team Scopus Importer:2022-04-15
Keywords: clinical characteristics; paediatric psoriasis; point-in-time sur-vey; psoriasis; real-world; unmet needs